Risk Factors for Higher Volume of Hemorrhage in Ruptured Anterior Circulation Intracranial Aneurysms - Ya, Xiaolong; Zhang, Chaoqi; Liu, Jichao; Zhang, Shuo; Zhang, Qian; Wang, Shuo; Cao, Yong; Zhao, Jizong (Frontiers in Surgery, 2020)
Purpose: To explore the influencing factors of volume hemorrhage in ruptured anterior circulation aneurysms, so as to identify the characteristics of anterior circulation aneurysms with high volume of hemorrhage, and to provide advice for clinical diagnosis and treatment for those aneurysms. Methods: From December 2012 to December 2017, a total of 1909 patients with intracranial aneurysm were treated in our center. According to the inclusion criteria, a total of 100 qualified patients were screened out. We collected demographic characteristics, environmental exposure, admission status of enrolled patients. In addition, morphological parameters and location of aneurysms were also included. The semi-automatic threshold method was used to measure the volume of hemorrhage. According to the results, the patients were divided into the group with high blood volume and low blood volume. Univariate and multivariate logistic regression analysis were used to discover the related factors affecting the bleeding volume. Results: In Univariable analysis, Whether to take anticoagulant drugs(P=0.044 <0.05), systolic blood pressure at admission (P=0.028) and pulse pressure (P=0.014) was shown significant difference at the P<0.05 test level, In terms of aneurysm morphology, the irregular shape (P< 0.001), calcification (P =0.001) and flow angle (P =0.006) shown significant statistical differences between the two groups at the P<0.01 level (P<0.01). Multivariate logistic regression analysis showed that irregular shape (OR = 5.370 P = 0.002 <0.05), large flow angle (OR = 1.033 P = 0.016 <0.05) and calcification (OR = 5.460 P = 0.003 <0.05) were risk factors for volume of hemorrhage in ruptured anterior circulation aneurysms. The influence of hypertension history was at critical state (OR=2.877 P=0.051>005). Conclusions： According to our analysis results, intracranial anterior circulation aneurysms with irregular shapes, calcifications and large flow angle are more dangerous. Aneurysms with these characteristics often have a large amount of hemorrhage, the clinical symptoms are more serious, and prognosis is worse. In addition, active and effective blood pressure management can also reduce the severity of the disease.